Find a home, lose a home: A research-based theatre journey into Acadian heritage - Shigematsu, Tetsuro; Göksel, Eva; Piazzoli, Erika; Belliveau, George; Naud, Philippe (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2025)
“Meet me in France to help me encounter my Acadian ancestors.” The Acadians were French settlers who established a unique culture in Atlantic Canada before being forcibly removed by the British in the 18th century. Taking up the invitation, five disparate artist/scholars gathered in France, but all their approaches would fit under the bigger tent of Research-based Theatre (RbT), an arts-based methodology in which embodied performances are created through the systematic research of real-life events and social issues. How does RbT serve to help us navigate the liminal space between research questions and the creation of theatre itself? If RbT is a term that encompasses a variety of approaches, how would grafting disparate artistic techniques transform our understandings of research?